Fenomena Culture Shock Mahasiswa Perantauan di Kabupaten Bekasi - Olivia, Helen; Sudarsono, Achmad Budiman; Sarasati, Fitri (Universitas Prof. Dr. Moestopo (Beragama), 2024)
When a person enters a new environment with a different culture, they experience culture shock because the customs, norms, customs, and principles they were previously familiar with cannot be applied. The purpose of this study was to find out how overseas students who experienced culture shock at Satya Negara Bekasi University adapted, as well as the factors that influenced the shock. The research method uses ethnographic methods and descriptive qualitative speech which is used to collect data by conducting interviews and documentation. The results showed that the conditions of overseas students differed in five phases of cultural adaptation. Bekasi students experienced cultural shock due to differences in socio-cultural conditions. However, choosing to stay alive and face current situations allows students to adapt to a new cultural environment. The components that affect culture, namely language, food, safety, and association are some of the factors that cause culture shock in students. So the most important factor is Language.